(untitled) (Innovative professional education, 2023)
The article is devoted to the problem of professional culture development in heads of structural divisions of postal enterprises. The need for constant and systematic training and professional development of managers, creation of conditions for innovation and changes in postal enterprises has been proven. It was concluded that the development of professional culture is a key element of the company’s development strategy, which allows attracting and supporting talented employees, ensuring high quality of products and services, strengthening the company’s position on the market and expanding business.